TINJAUAN PROSES KLAIM BPJS KESEHATAN DI UNIT RAWAT INAP RUMAH SAKIT ISLAM SUKAPURA JAKARTA UTARA TAHUN 2021 - Mei Nur Khasanah; Puteri Fannya; Laela Indawati; Daniel Happy Putra (Bajang Institute, 2023)
The National Health Insurance System (JKN) is a government program aimed at providing social welfare and protection for all Indonesian people. JKN is organized by the Social Security Organizing Agency (BPJS). The claim procedure is carried out by the coding officer and the hospital claims officer and then the completeness of the documents will be verified by the BPJS at the hospital. The research method carried out is a qualitative descriptive method, which aims to describe the state of the research object by conducting direct interviews on how the BPJS Health claim process of the Sukapura Islamic. Hospital Inpatient Unit to the BPJS Health. The results of observations through direct searches on claim files found that all claim files from October 2021 to December 2021 were 2,102 total claim files and 294 claim files were delayed. Part of the cause of the delay is that the coding of diagnoses and medical actions is not in accordance with the doctor's writing. Standard Operating Procedures (SPO) related to the BPJS Health claim process in inpatient care, specifically the Hospital already has SPO and has carried out activities according to SPO and that officer training is very influential on the delay factor in inpatient BPJS Health claim files.